HRM in Digital Transformation: Challenges and Opportunities in Adapting to Technological Change - Farida Farida (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Digital transformation compels businesses to adapt human resource management (HRM) practices, yet most research emphasizes developed economies, leaving challenges in developing countries underexplored. This study addresses this gap by examining how digital businesses in Indonesia manage HRM adaptation to technological change. Using a qualitative descriptive approach, secondary data were collected from scientific journals, books, and industry reports published between 2019 and 2024 and analyzed through data reduction, presentation, and conclusion drawing. Findings highlight three major challenges: non-standard work models, digital skill gaps, and data security risks, with 65% of Indonesian digital firms reporting difficulties in recruiting advanced digital talent. At the same time, opportunities arise from human resource information systems, global recruitment, and flexible work arrangements, with 40% of firms already leveraging international talent pools. The study concludes that effective HRM in digital businesses must prioritize digital skills training, foster innovation-driven cultures, and strengthen cybersecurity practices. By offering context-specific insights, this research contributes practical strategies for enhancing workforce adaptability and competitiveness in Indonesia’s digital economy, while also pointing to the need for further empirical studies on sector-specific HRM adaptation in developing countries.